Managing women with postnatal depression: Perceptions of the healthcare practitioners in Malaysia - Mohd Arifin, Siti Roshaidai (2017)
Background: Postnatal depression (PND) is considered to be a serious mental health problem for many women worldwide; contributing to increased maternal morbidity and mortality. It is recommended that healthcare practitioners (HCPs) should have appropriate skills to assess psychological distress in women attending for antenatal and postnatal healthcare. However, little is known about the perceptions of Malaysian HCPs towards managing PND. Purpose statement: The aims of this study was to explore how HCPs currently manage PND in Malaysia. Methods: A total of 18 HCPs involved with postnatal care in purposively selected clinics and a psychiatric ward in Kuala Lumpur, Malaysia were individually interviewed. Data were analysed using framework analysis. Findings: The explanations from the HCPs in the clinics showed that their care and treatment was limited by the absence of policy and guidelines for managing PND, that they could refer to. The absence of such guidelines had also resulted in an unclear job scope about whose role it was to manage PND. They also reported that the care and treatment for women with PND were challenging when a psychiatric referral and care was commonly stigmatised by the women and their family. The word ‘counselling’, ‘psychiatric ward’, and ‘antidepressants’ were reported as stigmatising and could be misunderstood to mean that a woman has a severe mental illness or that she was ‘crazy’. Conclusion: This study firstly calls for a policy and guideline for the management of PND within the Malaysian healthcare system to improve a sense of professional ownership for the management of PND. A system-based enhanced PND care is essential to ensure appropriate treatment and follow-up.